Acoustic and Microseismic Characterization in Steep Bedrock Permafrost on Matterhorn (CH) - Weber, Samuel; id_orcid:0 000-0003-0720-5378; Faillettaz, Jérome; Meyer, Matthias; id_orcid:0 000-0001-6895-2823; Beutel, Jan; id_orcid:0 000-0003-0879-2455; Vieli, Andreas (American Geophysical Union, 2018)
ISSN:0148-0227 ISSN:2169-9003 ISSN:2169-9011